Optimizing Student Admissions: Case Study of Integrated Islamic Private High School An-Nahl, Percikan Iman Jambi - Anita, Surya; Fitriani, Suci (Journal of Curriculum and Pedagogic Studies (JCPS), 2023)
This research aims to delineate the principal's strategic endeavors to enhance the student enrollment process at An-Nahl Percikan Iman Integrated Islamic Junior High School in Jambi. Employing a qualitative descriptive approach, data were gathered via observation, interviews, and documentation techniques. The analysis involved data reduction, presentation, and drawing conclu,;/.;sive insights. The findings reveal several key aspects: Firstly, student admissions at An-Nahl Percikan Iman Jambi Integrated Islamic Middle School are conducted both offline and online. Secondly, the management of admissions involves comprehensive planning, committee formation, criteria establishment, and varied promotional activities encompassing flyers, brochures, banners, billboards, and the setup of PPDB stands. Preparation entails facility administration, oral and written testing, implementation of activities such as BKA initiatives, school networking, parent engagement, and community outreach. Evaluation encompasses offline and online registration processes, emphasizing parent interviews crucial for fostering a conducive learning environment, culminating in student graduation announcements. Thirdly, the school principal fosters improvements in the admissions system through intensified communication with educators and stakeholders.